A guide to using the anonymous web in libraries and information organizations : enhancing patron privacy and information access - Lund, Brady, 1994-; Beckstrom, Matthew (Milton Park, Abingdon, Oxon ; New York : Routledge, 2022)
"A Guide to Using the Anonymous Web in Libraries and Information Organizations provides practical guidance to those who are interested in integrating the anonymous web into their services. It will be particularly useful to those seeking to promote enhanced privacy for their patrons. The book begins by explaining, in simple terms, what the anonymous web is, how it works, and its benefits for users. Lund and Beckstrom also explain why they believe access to the anonymous web should be provided in library and information organizations around the world. They describe how to provide access, as well as educate library users on how to utilize the anonymous web and navigate any challenges that might arise during implementation. The authors also encourage the development of library policies that guide appropriate conduct and filter content, where appropriate, in order to deter illegal activity. A Guide to Using the Anonymous Web in Libraries and Information Organizations reminds us that libraries and other information providers have a duty to educate and support their communities, while also preserving privacy. Demonstrating that the anonymous web can help them to fulfil these obligations, this book will be essential reading for library and information professionals working around the world"--
Introduction: The Anonymous Web and Libraries -- History of the Internet and Introduction to the Anonymous Web -- What is the Anonymous Web? -- History of Internet Privacy and Libraries -- Tor Around the World -- Integrating the Anonymous Web in Libraries and Information Organizations -- Anonymous Web Education -- A Role for Library and Information Science Researchers in Anonymous Web Research -- Case Examples of Anonymous Web Adoption in Information Organizations -- Conclusion: What Have We Learned? What Can We Do? -- Major Websites on the Anonymous Web -- The Big Glossary of the Anonymous Web and Related Topics.
OCLC-licensed vendor bibliographic record.
Keywords: Invisible Web; Dark Web; Libraries -- Information technology -- Security measures; Internet access for library users; Privacy, Right of; COMPUTERS / Computer Literacy; COMPUTERS / Internet / World Wide Web